2010
DOI: 10.4141/cjps09101
|View full text |Cite
|
Sign up to set email alerts
|

N, P, and S fertilization effects on industrial hemp in Saskatchewan

Abstract: S fertilization on industrial hemp in Saskatchewan. Can. J. Plant Sci. 90: 179Á184. Industrial hemp (Cannabis sativa L.) has become a well-known crop in western Canada in recent years, but insufficient information is available on its nutrient requirements for optimum yield. Our objective was to confirm the response of two hemp cultivars to increasing levels of nitrogen (N), phosphorus (P) and sulphur (S) in various sites in the province of Saskatchewan, during 2006Á2008. Increasing N rates significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 12 publications
(16 reference statements)
8
44
0
Order By: Relevance
“…The positive response of hemp biomass and seed yields to N fertilization we observed is in accordance with previous reports (Struik et al, 2000;Vera et al, 2004Vera et al, , 2010Mihoc et al, 2013). Research to date on the effects of N fertilization on biomass or seed composition is limited, but it was previously reported that N fertilization may have limited effects on biomass composition (Thomsen et al, 2005).…”
Section: Csupporting
confidence: 93%
See 2 more Smart Citations
“…The positive response of hemp biomass and seed yields to N fertilization we observed is in accordance with previous reports (Struik et al, 2000;Vera et al, 2004Vera et al, , 2010Mihoc et al, 2013). Research to date on the effects of N fertilization on biomass or seed composition is limited, but it was previously reported that N fertilization may have limited effects on biomass composition (Thomsen et al, 2005).…”
Section: Csupporting
confidence: 93%
“…Current recommendations for industrial hemp N fertilization in Western Canada range between 100 and 150 kg N ha −1 (Vera et al, 2004, 2010); our results suggest that in the province of Québec, N should be applied at higher levels. This conclusion is supported by Vera et al (2010), who hypothesized that greater N fertilization rates might be required for industrial hemp production in more humid environments than those in Western Canada. The evaluation of hemp response to N application rates above 200 kg N ha −1 in the typically more humid environments characteristic of Eastern Canada will, however, be required before definite recommendations can be made locally.…”
Section: Industrial Hemp Response To Nitrogen Fertilizationmentioning
confidence: 61%
See 1 more Smart Citation
“…In contrast, significant yield increases were reported in nitrogen limiting conditions (Van der Werf et al, 1995;Struik et al, 2000;Amaducci et al, 2002;Aubin et al, 2015). Vera et al (2010Vera et al ( , 2004 reported that hemp seed yield increased progressively with increasing nitrogen availability under a high fertilization rate, which ranged from 99 kg N ha −1 to 198 kg N ha −1 depending on growing conditions. According to several studies conducted in the Netherlands, England, Latvia and Italy, nitrogen fertilization rates ranged between 100 and 240 kg N ha -1…”
Section: Experimental Design and Treatmentsmentioning
confidence: 93%
“…These medicinal prescriptive uses in conjunction the expansion of indoor Cannabis propagation for psychoactive THC properties have stimulated the expansion of large indoor grow operations in several markets. Hemp is thought of as a relatively low input crop with limited demands for nutrients [7], but ensuring adequate supply of N, P, and K is critical to increase yields [8,9]. Indoor hydroponic and soil-less grow systems enable tight control over nutrient supply to plants, but several studies suggest that soil bacteria can facilitate nutrient uptake by plants, P in particular [10].…”
Section: Introductionmentioning
confidence: 99%